2005
DOI: 10.1039/b417717g
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzothiophene-S,S-dioxide–fluorene co-oligomers. Stable, highly-efficient blue emitters with improved electron affinity

Abstract: Incorporation of dibenzothiophene-S,S-dioxide units into conjugated fluorene oligomers changes the frontier orbital energy levels and presents an effective way to increase the electron affinity of these materials, which are highly fluorescent with bright blue emission in both solution and the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 24 publications
3
97
0
1
Order By: Relevance
“…This would explain why there are still no major LEP-based consumer products available in 2005. Note Added in Proof: After this paper was submitted, several important articles describing light-emitting properties of thiophene oligomers [134,135] and copolymers [136±142] were published.…”
Section: Discussionmentioning
confidence: 99%
“…This would explain why there are still no major LEP-based consumer products available in 2005. Note Added in Proof: After this paper was submitted, several important articles describing light-emitting properties of thiophene oligomers [134,135] and copolymers [136±142] were published.…”
Section: Discussionmentioning
confidence: 99%
“…2,7-Dibromo-9,9-dioctylfluorene (F8) and 9,9-dioctylfluorene-2,7-diboronic acid bis(1,3-propanediol) ester, 4,7-bis-(5-bromo-2-thienyl)-2,1,3-benzothiadizole and 3,7-dibromodibenzothiophene-S,S-dioxide were either synthesized using literature routes [31] or purchased from Sigma-Aldrich and purified by repeated recrystallisations. [31,32] A general method for the preparation of the polymers on a 1 gram scale can be found in the Supporting Information. In similar polymers it has been reported that exceeding 0.05 mol % of TBT results in complete energy transfer to the red unit.…”
Section: Methodsmentioning
confidence: 99%
“…Now it is known that the green shift can be attributed to the formation of fluorenone (Figure 34) defects in the chain Lupton, Craig, and Meijer 2002;Gamerith et al 2004]. This discovery has resulted in the design of new polymers that prevent the formation of the fluorenone defect [McKiernan, Towns, and Holmes 2005;Perepichka et al 2005]. Scientists spent years discussing the cause of the green shift, in part because of the lack of tools capable of analyzing the formation of a small density of defects in an operating device.…”
Section: Background and Motivationmentioning
confidence: 99%